2003
DOI: 10.1021/jp030188j
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Behavior and Magnetic Properties of a Nitroxide Amino Acid Derivative in Vacuo and in Aqueous Solution

Abstract: The conformational behavior and magnetic properties of the R-acetylamino, N′-methylamide derivative of TOAC (4-amino-2,2,6.6-tetramethylpiperidine-1-oxyl-4-carboxylic acid) have been investigated in vacuo and in aqueous solution by an integrated computational approach including density functional, post-Hartree-Fock, and continuum solvent models. According to our computations, piperidine rings with an equatorial placement of the nitroxide moiety are more stable by about 1 kcal/mol than their axial counterparts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…A quantum mechanical study of TOAC in vacuo and in aqueous solution showed that the nitroxyl group in an equatorial position is more stable than in the axial position (D'Amore et al 2003). In addition, the crystallographic characterization of some TOAC derivatives showed the piperidine ring in an approximate chair conformation, with the α-amino group in the axial position and the α-carboxyl group in the equatorial position (Flippen-Anderson et al 1996; Crisma et al 2005).…”
Section: Toac and Toac-containing Peptides: Synthesis And Structuralmentioning
confidence: 99%
“…A quantum mechanical study of TOAC in vacuo and in aqueous solution showed that the nitroxyl group in an equatorial position is more stable than in the axial position (D'Amore et al 2003). In addition, the crystallographic characterization of some TOAC derivatives showed the piperidine ring in an approximate chair conformation, with the α-amino group in the axial position and the α-carboxyl group in the equatorial position (Flippen-Anderson et al 1996; Crisma et al 2005).…”
Section: Toac and Toac-containing Peptides: Synthesis And Structuralmentioning
confidence: 99%
“…While some gradient corrected approximations ͑GGA͒ provide reasonable numerical values for hfc's, 12 several studies have shown that a particular approach to DFT, the so-called hybrid Hartree-Fock/Kohn-Sham ͑HF/KS͒ model, 16 introduces further significant improvements. [17][18][19][20] As a matter of fact, the calculation of hfcs is now a standard feature of many quana͒ Author to whom correspondence should be addressed. Electronic mail: baronev@unina.it tum chemical packages and can be easily and routinely performed.…”
Section: Complete Structural and Magnetic Characterization Of Biologimentioning
confidence: 99%
“…Geometry optimizations for each selected conformer were then performed by means of density functional theory (DFT) at the B3LYP/6-31G(d) level as implemented in the GAUSSIAN 03 package, because it is well known that computational models based on DFT are particularly suitable for the analysis of magnetic properties for open-shell species. [62][63][64][65][66] Energetics was further studied in aqueous solution via polarizable continuum model (PCM) using single-point energy calculations at the B3LYP/6-31G+(d,p) level. [67] A scaling factor of 0.9806 was used for the zero-point vibrational energy (ZPE) correction for the B3LYP geometries.…”
Section: Theoretical Calculationsmentioning
confidence: 99%